Association between antenatal care utilization with severe maternal and perinatal morbidity - Deshpande, Sonali; Khedekar, Mohini; Gadappa, Shrinivas; Badgire, Swati (Nepal Journal of Obstetrics and Gynaecology, 2020)
Aim: To analyse association between adequate antenatal care utilization with severe maternal morbidity and severe perinatal morbidity. Methods: The prospective observational study was conducted in a Government medical college and hospital, Aurangabad from 1st October 2017 to 30th September 2019 after Institution Ethics Committee approval. Pregnancy after 28 weeks without pre-existing medical disorder and fetal anomaly were studied. The data were analyzed to find out the association between adequate antenatal care utilization and severe maternal and severe perinatal morbidity by using chi-squared test. Results: Among 500 participants, 243 (48.6%) had adequate visits. Women with inadequate antenatal care utilization were at higher risk of preterm delivery, severe maternal and perinatal morbidity. Conclusions: Inadequate antenatal care is can predict increased severity of maternal and perinatal morbidity. Keywords: Antenatal care utilization, focused antenatal care, severe maternal morbidity, severe perinatal morbidity